2006
DOI: 10.1007/s10823-006-9021-3
|View full text |Cite
|
Sign up to set email alerts
|

Language Barriers Surrounding Medication Use among Older Latinos

Abstract: Limited English language proficiency forms a significant challenge for many Latinos in clinical settings. Although medications are commonly used by older individuals as a means of maintaining good health and managing health problems, the extent to which English proficiency is related to medication use among older Latinos is not known. Focus groups were conducted with Latino, community-residing individuals aged 50 and over in eastern Massachusetts. Qualitative evaluation of the group interviews suggests that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…35 In order to find solutions to pharmacy-related health disparities with Spanishspeaking Latinos, it is imperative to determine the perceptions of this population of patients. Problems with pharmacy communication services have been linked to the lack of professional interpretation 37 and translation services by pharmacists, 38 and the lack of these services has led to low levels of satisfaction in Spanish-speaking patients. 39 Sleath et al 35 found that abiding by certain cultural normative values, such as simpatía (kindness or politeness), personalismo (formal friendliness), and respeto (respect) were important to Latino patients.…”
Section: S) It Has Been Established That Americanmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In order to find solutions to pharmacy-related health disparities with Spanishspeaking Latinos, it is imperative to determine the perceptions of this population of patients. Problems with pharmacy communication services have been linked to the lack of professional interpretation 37 and translation services by pharmacists, 38 and the lack of these services has led to low levels of satisfaction in Spanish-speaking patients. 39 Sleath et al 35 found that abiding by certain cultural normative values, such as simpatía (kindness or politeness), personalismo (formal friendliness), and respeto (respect) were important to Latino patients.…”
Section: S) It Has Been Established That Americanmentioning
confidence: 99%
“…37 Other pharmacy related-problems stem from the lack of written translation services in Spanish and Spanish-speaking pharmacy employees. 38,84,133 Specifically, the inability of healthcare providers to listen to Spanish-speaking patients, answer questions, and provide explanations about prescription medications and medical tests has led to significant levels of dissatisfaction with medical providers.…”
Section: Section 6: Summary Of Relevant Literaturementioning
confidence: 99%
“…These findings are further supported by a 2007 study of elderly Spanish-speaking patients in Boston, where patients felt that limited English proficiency decreased patient care. 4 Outcomes studies have reinforced these findings. A large systematic review of these studies found that lack of bilingual health care providers or trained medical interpreters has negative effects on patient outcomes, including poor adherence to medications, increased medication errors, unnecessary diagnostic tests, and poor follow up after hospitalization.…”
Section: Introductionmentioning
confidence: 89%
“…40 The use of professional interpreters is associated with improved clinical care and patient satisfaction more than is use of ad hoc interpreters, 41 but overall, the presence of a third person (i.e., an interpreter) in a confidential relationship changes things. It influences both transference and countertransference between individuals involved, with unavoidable consequences on a doctor-patient relationship.…”
Section: What Do We Do With Such a 'Model' Today?mentioning
confidence: 99%